Pengaruh Penggunaan Yea-Sacc®1026 Terhadap Performans Sapi Potong - Rahmat Hidayat; De Iwan Rahwanandi (Pusat Publikasi Jurnal Universitas Islam Kalimantan, 2013)
The aim of research is to find out the influence of probiotic utilization in the ration on dry metter intake, average daily gain (ADG), carcas percentage and economical value. The research was done in 90 days. Probiotic that used in this research is Yea-sacc®1026, commercial product from PT. Alltech. Yea-sacc®1026 contains Saccharomyces cerevisiae strain 1026 and its growth medium. There are two kinds of ration formula (formula I and II). One of each ration was given yeasacc®1026 1kg/1000 kg, and the other was not given, so there are 4 ration treatments. This research used Brahman Cross breed (steer and heifer). Each treatment used 30 heads of beef cattle, so there are 120 heads of beef cattle. The size of paddock 10 x 10m. This research used randomized completely design with 30 replications. The datta were analyzed by The SAS System for Windows 6.12. and then Duncan Multiple Range Test. The result of the research indicated that the formulation ( I and II) and Yea-sacc®1026 used had no effect to dry metter intake, average daily gain (ADG), carcas percentage and economical value.